Queues Are Databases - Gray, Jim (1995)
Message-oriented-middleware (MOM) has become an small industry. MOM offers queued transaction processing as an advance over pure client-server transaction processing. This note makes four points: Queued transaction processing is less general than direct transaction processing. Queued systems are built on top of direct systems. You cannot build a direct system atop a queued system. It is difficult to build direct, conversational, or distributed transactions atop a queued system. Queues are interesting databases with interesting concurrency control. It is best to build these mechanisms into a standard database system so other applications can use these interesting features. Queue systems need DBMS functionality. Queues need security, configuration, performance monitoring, recovery, and reorganization utilities. Database systems already have these features. A full-function MOM system duplicates these database features. Queue managers are simple TP-monitors managing server pools driven by queues. Database systems are encompassing many server pool features as they evolve to TP-lite systems.